Faktor-Faktor yang Berhubungan dengan Status Imunisasi Lanjutan Campak di Wilayah Kerja Puskesmas Labuhan Ratu Kota Bandar Lampung Tahun 2018 - Arini Meronica; Roro Rukmi Windi Perdani; Susianti (MAJORITY, 2021)
Advanced measles immunization is a health program held by the government for ncreasing the level of immunity and extending the period of protection given to children under the age of three and school-age children. The corevage advanced measles immunization at Labuhan Ratu Primary Health Center is the lowest in Bandar Lampung, which is caused by immunization providing behaviour of the mother which is influenced by some factors such as mother's knowledge, mother's attitude, mother's job status, affordability of health services and the role of health workers.This study was an observational study with a cross sectional design. There were 42 respondents which are determined by purposive sampling method. The data was assessed by questionnaire and collected by interview. The data was analyzed univariate and bivariate. Bivariate analysis using chi square test. The results showed 35.7% of respondents received incomplete immunization. Bivariate analysis showed the variables associated with sustainable immunization were knowledge (p value 0.002) and maternal attitudes (p value 0.001). Bivariate analysis also showed that the mother’s employment status (p value 0.47), affordability of the health service place (p value 0.287) and the role of health workers (p value 0.357) were not related. The conclusion is that mother’s knowledge and mother’s attitude were the factors correlated to advanced measles immunization.